Distinct impacts of tropical North Atlantic warming flavors on cross-basin tropical cyclone activity. - Zhao,J; Bai,L; Zhan,R; Liu,Y; Cai,W; Wang,Y; Kug,J-S; Moon,I-J; Feng,X; Toumi,R; Zhou,B; Zhang,L; et al. (Sci Adv, 2026)
Tropical North Atlantic (TNA) warming typically favors tropical cyclone (TC) genesis over the North Atlantic but suppresses TC formation over the Northwest Pacific during boreal summer. The TNA anomaly patterns can be classified into an eastern coastal and a western warm-pool type, but their respective impacts remain unclear. Here, we find a pronounced difference in the impact between the two TNA flavors. The warm-pool TNA warming suppresses Northwest Pacific TC genesis through a remote dynamical control, while the coastal warming promotes North Atlantic TC genesis via a local thermodynamic control. High-resolution modeling reveals that, compared with the canonical TNA warming, the warm-pool TNA warming suppresses Northwest Pacific TC genesis by 65.2%, while the coastal warming enhances North Atlantic TC genesis by 60.1%. Under greenhouse warming, increased coastal TNA warming is projected to intensify North Atlantic TC activity. Therefore, distinguishing TNA flavors is critical for improving seasonal prediction and future projections of cross-basin TC activity.